Stress in Post-War Britain - Jackson, Mark (Studies for the Society for the Social History of Medicine, 2015)
In the years following World War II the health and well-being of the nation was of primary concern to the British government. The essays in this collection examine the relationship between health and stress in post-war Britain through a series of carefully connected case studies.